Risk Factors for Intensive Care Unit Admission in Patients with Autoimmune Encephalitis - Harutyunyan, Gayane; Hauer, Larissa; Dünser, Martin W.; Moser, Tobias; Pikija, Slaven; Leitinger, Markus; Novak, Helmut F.; Aichhorn, Wolfgang; Trinka, Eugen; Sellner, Johann (Frontiers in Immunology, 2017)
Background Prevention and early recognition of critical illness in patients with autoimmune encephalitis (AE) is essential to achieve better outcome. Aim of the study To evaluate risk factors for intensive care unit (ICU) admission and its prognostic impact in patients with autoimmune encephalitis (AE). Patients and Methods A reclassification of patients hospitalized between 2011 and 2016 revealed 17 “definite” and 15 “probable” AE cases. Thirteen patients (41%) developed critical illness and required ICU care. The underlying conditions were intractable seizures or status epilepticus (54%), altered mental state (39%) and respiratory failure (8%). Results ICU admission was associated with longer time from first symptoms to hospitalization (p=0.046). Regression analysis revealed that anaemia on admission and detection of neuronal antibodies was associated with a higher risk of ICU . At last follow-up after a median of 31 months (range 2.5–52.4), seven patients had died (23%) and 63% had a good outcome (modified Rankin Scale 0-3). Anaemia was associated with poor prognosis (p=0.021), whereas development of critical illness did not impact mortality and functional outcome. Conclusion We confirmed the need for ICU care in a subgroup of patients and the prevailing objective is improved seizure control, and the presence of neuronal antibodies and anaemia were identified as risk factors for development of critical illness. However, ICU admission did not affect outcome.